Efficacy of red cell distribution width and plateletcrit as predictors of subclinical inflammation in obesity (Annals of Medical Research, 2021)
Aim: The present study aimed to investigate the relationship of the hematological predictors of inflammation in complete blood count with body mass index (BMI) and homeostatic model assessment for insulin resistance (HOMA-IR) values.Material and Methods: The study included 354 subjects, who were admitted to the endocrinology outpatient clinic between January 2016 and March 2018. According to their BMI values, the subjects were divided into five groups as class III obesity, class II obesity, class I obesity, overweight, and normoweight. In addition, the subjects were divided into two groups as HOMA-IR 2.7 and HOMA-IR ≥2.7 to evaluate insulin resistance. Medical records of all the patients were reviewed and the data were collected retrospectively. As the predictors of subclinical inflammation, the mean platelet volume (MPV), platelet distribution width (PDW), plateletcrit (PCT), red cell distribution width (RDW), neutrophil-lymphocyte ratio (NLR), and platelet-lymphocyte ratio (PLR) were compared among the study groups.Results:There were statistically significant differences among the BMI groups in terms of WBC, neutrophil count, lymphocyte count, RDW, platelet count, and PCT values. Hemoglobin, WBC, neutrophil count, lymphocyte count, RDW, platelet count, and PCT value were significantly higher in those having HOMA-IR value of ≥2.7. Multivariate linear regression analysis revealed significant correlations of BMI with RDW and PCT values, whereas HOMA-IR showed a correlation only with PCT value.Conclusion: RDW and PCT are simple and low-cost markers that are able to predict the development of cardiovascular complications and other comorbidities in overweight and obese subjects.
Keywords: Obesity; homeostatic model assessment for insulin resistance; subclinical inflammation; red cell distribution width; plateletcrit.